Representation Of Feminism In Kretek Girl Serial Film Episode 2 - Yuliwar, Yohanes Sonnie; Harahap, Halomoan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This study aims to analyze the representation of feminism in Gadis Kretek episode 2, focusing on how women are depicted through narrative, visuals, and dialogue. This study also explores whether female characters have full agency or are subject to the male gaze, and how social, cultural, and class factors influence these representations. In addition, this study compares the representation of feminism in Gadis Kretek with other films or series in Indonesia, and assesses its impact on audience perceptions of feminism and the role of women in Indonesia. The method used in this study is John Fiske's semiotic approach, which focuses on the analysis of signs in media texts, both in narrative and visual aspects. This method is integrated with feminist theory, especially the concept of the "male gaze" from Laura Mulvey and intersectionality from bell hooks. This approach allows researchers to uncover the meaning behind the representation of women in the series and how gender power dynamics are played out. The conclusion of this study shows that Gadis Kretek represents feminism through a process of negotiation between patriarchal norms and women's resistance. The female characters in this series have power and agency, but remain bound by a patriarchal social system. In addition, class and cultural factors influence this representation, where women from different social backgrounds experience feminism in different ways. The series influences the audience's perception of feminism by providing a realistic depiction of women's roles in Indonesia's patriarchal society.